2016
DOI: 10.1039/c6cp03616c
|View full text |Cite
|
Sign up to set email alerts
|

Alcohols as molecular probes in ionic liquids: evidence for nanostructuration

Abstract: A comprehensive study of the solution and solvation of linear alcohols (propan-1-ol, butan-1-ol and pentan-1-ol) in ionic liquids (ILs) is presented. The effect of the alkyl chain size of both alcohols and ILs (1-alkyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [CnC1im][NTf2], ionic liquid series) on the thermodynamic properties of solution and solvation was used to obtain insight into the interactions between alcohols and ILs. Alcohols were used as molecular probes to ascertain whether their solva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 77 publications
4
20
1
Order By: Relevance
“…The mutual solubility of imidazolium ILs and alcohols are intrinsically related to significant interactions of ILs with alcohols. , These interactions are important characters affecting physicochemical behaviors of IL–alcohol mixtures. , A general feature is that a gradual lengthening of alcohol alkyl chains leads to a systematic decrease in solubility of ILs in alcohols, which is deduced from solubility of [C 2 MIM]­[NTF 2 ] in propanol, butanol, and pentanol, and of [C 8 MIM]­[BF 4 ] in butanol and pentanol, as well as solubility of other ILs containing different cation–anion moieties in various alcohols. ,, Lengthening alcohol alkyl chains leads to a decrease in excess molar enthalpies and increases in molar excess volumes and in upper critical solution temperature (UCST) of IL–alcohol mixtures. These properties indicate that packing structures and interactions between unlike molecules become less important in mixtures containing long chain alcohols. , By contrast, an increase in alkyl chain length in imidazolium cations leads to enhanced hydrophobicity of ILs and therefore results in a decrease in UCST of IL–alcohol mixtures. ,, Decreasing HB opportunities of alcohols with C(2)-methylated imidazolium cations results in an increase in UCST, while the coupled anions have a significant impact on this property, , which diminishes with increasing alkyl chain length in cations. ,, …”
Section: Ionic Liquid–molecular Solvent Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutual solubility of imidazolium ILs and alcohols are intrinsically related to significant interactions of ILs with alcohols. , These interactions are important characters affecting physicochemical behaviors of IL–alcohol mixtures. , A general feature is that a gradual lengthening of alcohol alkyl chains leads to a systematic decrease in solubility of ILs in alcohols, which is deduced from solubility of [C 2 MIM]­[NTF 2 ] in propanol, butanol, and pentanol, and of [C 8 MIM]­[BF 4 ] in butanol and pentanol, as well as solubility of other ILs containing different cation–anion moieties in various alcohols. ,, Lengthening alcohol alkyl chains leads to a decrease in excess molar enthalpies and increases in molar excess volumes and in upper critical solution temperature (UCST) of IL–alcohol mixtures. These properties indicate that packing structures and interactions between unlike molecules become less important in mixtures containing long chain alcohols. , By contrast, an increase in alkyl chain length in imidazolium cations leads to enhanced hydrophobicity of ILs and therefore results in a decrease in UCST of IL–alcohol mixtures. ,, Decreasing HB opportunities of alcohols with C(2)-methylated imidazolium cations results in an increase in UCST, while the coupled anions have a significant impact on this property, , which diminishes with increasing alkyl chain length in cations. ,, …”
Section: Ionic Liquid–molecular Solvent Mixturesmentioning
confidence: 99%
“…This trend of increasing exothermic enthalpies from [C 4 MIM]­[PF 6 ] to [C 4 MIM]­[TFA] is rationalized by a decrease in cavitation energy (endothermic contribution) and an increase in IL–alcohol interaction strength (exothermic contribution). In addition, variations in molar enthalpies of solvation of propanol in [C 4 MIM] ILs are linearly correlated with HB interactions of anions with propanol in IL–propanol mixtures. , These experimental and computational results are generally consistent with previous findings on delicate interactions of different solutes with anions in protic and aprotic ILs. ,, …”
Section: Ionic Liquid–molecular Solvent Mixturesmentioning
confidence: 99%
“…Vaz et al [20] found experimental evidence of nanostructuration using alcohols as a probe of the RTIL structure in mixtures. Scharf et al [21] studied ion pairing and the dynamics of the RTIL in chloroformmixtures using NMR.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the work reported until now is mainly related to imidazolium- or pyridinium-based ILs combined with [Cl] − , [BF 4 ] − , [PF 6 ] − , or [NTf 2 ] − . Despite of the intense research, many data found in the literature are not of the highest quality due to the use of different experimental methodologies (e.g., scanning rates, annealing periods, sample size, thermal history, and sample purity). It is well accepted that ILs are structured fluids due to the complexity of their organization and diversity of the nature of their molecular interactions, showing high- and low-charge density regions. The understanding of the nanostructuration of ILs and its intrinsic relation to most of their physicochemical properties is fundamental to achieve the possibility of tuning an ionic liquid to a specific functionality or application without endless screening and trial and error. The effects of nanostructuration have been detected in several physicochemical properties, such as heat capacities, , densities, surface tensions, , viscosities, , thermal behavior, ,, and vapor pressures, among others . For all these properties a trend shift was observed at the same critical value for the number of carbons of the alkyl chain N = 6, named as the critical alkyl size (CAS). ,,,,, Pyridinium based ILs have a high potential of applicability , due to their high thermal stability and the aromatic character of the cation, exhibiting physical-chemical properties very similar to those of the imidazolium cation analogues. Nevertheless, the replacement of the imidazolium by the pyridinium cation modifies the structural organization of the liquid phase, affecting the physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of nanostructuration have been detected in several physicochemical properties, such as heat capacities, 12,20−23 densities, surface tensions, 24,25 viscosities, 21,26−32 thermal behavior, 12,13,33−36 and vapor pressures, 37−40 among others. 41 For all these properties a trend shift was observed at the same critical value for the number of carbons of the alkyl chain N = 6, named as the critical alkyl size (CAS). 12,13,27,37,42,43 Pyridinium based ILs have a high potential of applicability 44,45 due to their high thermal stability and the aromatic character of the cation, exhibiting physical-chemical properties very similar to those of the imidazolium cation analogues.…”
Section: ■ Introductionmentioning
confidence: 99%